Inclusions Involving Interval-Valued Harmonically Co-Ordinated Convex Functions and Raina’s Fractional Double Integrals - Bandar Bin Mohsin; Muhammad Uzair Awan; Muhammad Zakria Javed; Hüseyin Budak; Awais Gul Khan; Muhammad Aslam Noor (Journal of Mathematics)
The aim of this article is to obtain some new integral inclusions essentially using the interval-valued harmonically co-ordinated convex functions and κ-Raina’s fractional double integrals. To show the validity of our theoretical results, we also give some numerical examples.